Morpho-anatomical characteristics, phytochemical and antibacterial potential of Sargassum polycystum collected along the southern coast of Java, Indonesia - MARIA DYAH NUR MEINITA; RISKI YULIA; MUHAMMAD NURSID; NUNUK ARIES NURULITA; DICKY HARWANTO; RIVIANI RIVIANI; RIYANTI RIYANTI (Society for Indonesian Biodiversity, 2024)
Abstract. Meinita MDN, Yulia R, Nursid M, Nurulita NA, Harwanto D, Riviani, Riyanti. 2024. Morpho-anatomical characteristics, phytochemical and antibacterial potential of Sargassum polycystum collected along the south coast of Java, Indonesia. Biodiversitas 25: 2669-2681. The southern coast of Java is one of the coastal areas in Indonesia with a high abundance of seaweed. Sargassum polycystum, a brown marine macroalga that is abundant in southern coast of Java, contains high secondary metabolites and exhibits promising potential as an antibacterial agent. There is lack of comprehensive study on morpho-anatomical characteristic and bioactivity of S. polycystum. Hence, this study investigated the morpho-anatomical characteristics, phytochemical compound content, and antibacterial activity of S. polycystum collected from three different beaches along the southern coast of Java Island against pathogenic bacteria Bacillus megaterium, Micrococcus luteus, and Escherichia coli. Specimen collection was done using purposive random sampling along southern coast of Java Island, followed by descriptive exploratory of morpho-anatomical characteristic, extraction, phytochemical analysis and antibacterial activity assay. Maceration with methanol solvent during 48 hours was used for extraction. The phytochemical analysis employed a qualitative descriptive method, while the antibacterial activity was assessed using the disc diffusion method (Kirby-Bauer). The morpho-anatomical characteristics observed of S. polycystum include the characteristic of a rough-textured stipe, round tapered serrated blade, small disc-shaped holdfast, alternate pinnate branching, cell wall, vacuole and cytoplasm. The morphology and anatomy of S. polycystum particularly the thallus and blade structure are strongly impacted by the environmental condition of southern coast of Java. Phytochemical analysis revealed the presence of alkaloids, flavonoids, saponins, and steroids in S. polycystum extract. Antibacterial assay demonstrated a medium to strong antibacterial activity against B. megaterium with bacteriostatic properties, strong to very strong antibacterial activity against M. luteus, and weak antibacterial activity against E. coli. Future research is required to examine how environmental conditions affect the composition and concentration of phytochemical compounds in S. polycystum.